UPLC-ESI/MSn metabolic profiling of Cedrela odorata L. and Toona ciliata M. Roem and in vitro investigation of their anti-diabetic activity supported with molecular docking studies - Heba A. S. El-Nashar; Ayman M. Al-Qaaneh; Ayman M. Al-Qaaneh; Md. Shimul Bhuia; Md. Shimul Bhuia; Raihan Chowdhury; Raihan Chowdhury; Mostafa A. Abdel-Maksoud; Hossam Ebaid; Abdul Malik; Muhammad Torequl Islam; Muhammad Torequl Islam; et al. (Frontiers in Chemistry)
IntroductionThe genus Cedrela is one of the phytochemically rich genera of the family Meliaceae. In this study, two Cedrela species, namely, Cedrela odorata and Toona ciliata M. Roem (formerly Cedrela toona), were selected for in-depth phytochemical profiling with the aid of UPLC-ESI/MSn analysis followed by evaluation of their anti-diabetic potential through assessment of in vitro α-amylase and α-glucosidase inhibitory effects, alongside the molecular docking studies on these target enzymes.Materials and methodsUPLC-ESI/MSn technique was applied to tentatively identify the extracts. The anti-diabetic properties were assessed using BioVision α-amylase and α-glucosidase inhibitor screening kits. Further, the molecular docking studies utilized PyRx® and Discovery Studio software.Results and discussionThe UPLC-ESI/MSn analysis led to the identification and quantification of 55 metabolites with their fragmentation patterns for the first time for these two species. Flavonoids represented the main identified class, followed by phenylpropanoids, terpenes, tannins, and others. The two species showed potent enzyme inhibition, where C. odorata and C. toona significantly inhibited α-amylase (IC50 = 4.83 ± 0.01 and 3.50 ± 0.03 μg/mL) compared to pioglitazone (IC50 = 2.17 ± 0.23 μg/mL), while their α-glycosidase inhibitory properties were also potent with (IC50 = 7.17 ± 0.01 and 6.50 ± 0.69 μg/mL), respectively, compared to acarbose (IC50 = 4.83 ± 1.02 μg/mL). The enzyme inhibitory activities were further confirmed by in silico molecular docking of the main identified components with the respective binding sockets in both α-amylase and α-glycosidase enzymes.ConclusionThese promising results could pave the way for a novel discovery of natural phytoconstituents with potent anti-diabetic activity.